Technologies and trust - Giannandrea, Lorella (Media e tecnologie per la didattica - Open Access, 2017)
What is trust and how new technologies are changing or affecting the concept of trust? This publication offers insights from researchers working in educational technology and distance education, collected in the frame of the European FP-7 Marie-Curie People project "Stimulators and inhibitors of a culture of trust in educational interactions assisted by modern information and communication technology", and provides examples of implications of trust for successful learning experiences in distance education. The research goal is to understand how trust has changed or is changing: this is related not only to the modification of the meaning, but also indicators upon which people built their judgements.